THE IMPACT OF VARIATIONS IN CLINICAL PATHWAY IMPLEMENTATION ON POTENTIAL REVENUE LOSS FROM CESAREAN SECTION SERVICES AT DR. SAIFUL ANWAR REGIONAL HOSPITAL, EAST JAVA, INDONESIA - Indrawan, I Wayan Agung; Setijowati, Nanik; Rahmah, Shofi Nur (Universitas Brawijaya, 2025)
This study examines the impact of variations in clinical pathway (CP) implementation on potential financial losses in Sectio Caesarea (SC) services at Dr. Saiful Anwar Regional Hospital, East Java, Indonesia. Applying a quantitative approach with a cross-sectional study design, secondary data in the form of medical records and patient treatment costs were analyzed using the categorical comparative method from February to May 2024. The results showed that the majority of patients (78.4%) had good compliance with CP, while 21.6% did not comply. The group with appropriate CP implementation showed a lower average hospital cost (IDR 24,435,564.29) compared to the non-compliant group (IDR 30,996,638.89). CP implementation variance significantly affected cost containment, where the compliant group had a smaller average deficit (-IDR 15,741,421.43) compared to the non-compliant group (-IDR 20,243,246.30). Logistic regression tests showed that the more appropriate the CP, the greater the cost efficiency achieved. However, demographic factors and patient clinical conditions did not significantly affect the implementation of CP. This study concludes that proper CP implementation enhances cost efficiency and reduces potential hospital losses in SC actions. Finally, evaluation and development of evidence-based CP and periodic monitoring of its implementation are recommended to improve the efficiency of hospital services.